Pengaruh Umur dan Jenis Kelamin Itik Alabio Terhadap Nilai Energi Metabolis dan Retensi Nitrogen Bungkil Maggot Hermetia illucens - Aam Gunawan; Muhammad Syarif Djaya; Raga Samudera (Universitas Sebelas Maret (UNS), 2018)
Maggot black soldier fly extracted (Hermetia illucens) were mechanical extracted from maggot meal, so that the fat content of the maggot extracted is lower than the maggot meal. Quality protein and metabolizable energy content maggot extracted is not yet known, but important for poultry feed formulations. Therefore, this study aims to determine the value of apparent metabolizable energy corrected for nitrogen (AMEn) and nitrogen retention maggot extracted is experimentedat male and female duck at various ages of duck. The study used 32 Alabio duck placed in individual cages. The design used was randomized block design with four treatments and four replications. Data obtained were analyzed variance and Duncan's multiple range test. The treatments experimented consisted of P1: the ducks age of4 weeks, P2: the ducks age of 8 weeks, P3: the ducks age of 12 weeks, and P4: the ducks age of 24 weeks. The results of this research showed that the age of ducks effect the value of metabolizable energy and nitrogen retention maggot extracted, whereas sex are not significant effect(P>0.05). It can be concluded thatthe content of metabolizable energy and nitrogen retention maggot extracted at 8-24 weeks of age ducks are relatively similar, while at the age of 4 weeks ducks metabolizable energy content and nitrogen retention lower than the ducks age of 8-24 weeks.